Metabolically Healthy Obesity Is Associated with an Increased Risk of Colorectal Adenoma Occurrence Diagnosed by Surveillance Colonoscopy - Hyunbeom Chae; Hyo-Joon Yang; Soo-Kyung Park; Yoon Suk Jung; Jung Ho Park; Dong Il Park; Chong Il Sohn (Gut and Liver, 2021)
Background/Aims: The risk of recurrence of colorectal adenoma among obese individuals without metabolic abnormalities or in those with metabolically healthy obesity is largely unexplored. Therefore, we longitudinally investigated the risk of adenoma occurrence in individuals undergoing surveillance colonoscopy according to metabolic status and obesity. Methods: This retrospective cohort study included 16,872 Korean adults who underwent their first screening colonoscopy between 2003 and 2012 and who then underwent follow-up colonoscopy until 2017. Participants were categorized into a metabolically healthy nonobese group (reference group), a metabolically healthy obese group, a metabolically abnormal nonobese group, and a metabolically abnormal obese group. Hazard ratios (HRs) for adenoma recurrence compared to the reference group were calculated in each group. Results: During a median follow-up duration of 47.3 months (interquartile range, 35.6 to 58.9 months), 3,673 (21.8%) and 292 (1.73%) participants developed adenoma and advanced adenoma, respectively. When age, sex, smoking, alcohol consumption, family history of colorectal cancer, and baseline adenoma risk were adjusted, the risk of adenoma recurrence was increased in metabolically healthy obese individuals (HR, 1.33; 95% confidence interval [CI], 1.12 to 1.57) and metabolically abnormal obese individuals (HR, 1.18; 95% CI, 1.08 to 1.30) but not in metabolically abnormal nonobese individuals (HR, 1.03; 95% CI, 0.94 to 1.13). Conclusions: In this study, metabolically healthy obese individuals and metabolically abnormal obese individuals exhibited increased risks of occurrence of colorectal adenoma diagnosed by surveillance colonoscopy. This finding implies that obesity itself, even without metabolic abnormalities, is associated with an increased risk of adenoma recurrence.